CANAL TRANSPORT INDEX AND ROOT CANAL CENTRALIZATION CAPACITY PROMOTED BY THE BIORACE, V-FILE, AND PROTAPER NEXT SYSTEMS: A CBCT STUDY (CIPEEX, 2025)
Objective: This study aims to analyze the transport index (TI) and centralization capacity (CC) of root canal preparation using different nickel-titanium instruments, based on images obtained by cone beam computed tomography (CBCT). Material and Methods: Forty-five mesiobuccal canals of lower molars were prototyped. Groups: The canals were randomly distributed into three groups (n=15) according to the rotary instrument used: G1: BioRace®, G2: V-File®, G3: Protaper Next®. CBCT images were obtained before and after canal preparation. Measurements were performed by two examiners using OsiriX® DICOM Viewer software. The analyses were performed 3 mm below the furcation of the teeth. The IT and CC were evaluated according to the methodology proposed by Gambill et al. (1996). The data obtained were analyzed using the Kruskal-Wallis test, with a significance level of 5%. Results: All instruments analyzed caused root canal transport and decentralization. BioRace® and V-File®: Tendency toward distal transport. Protaper Next®: Tendency toward mesial transport. No significant differences were found between the groups in terms of IT and CC (p
Keywords: Root canal preparation; Endodontics; Cone beam computed tomography; Treatment failure